Formal Logic and Flowchart for Diagnosis Validity Verification and Inclusion in Clinical Decision Support Systems. (April 2016) - Sosa, M; Grundel, L; Simini, F
Abstract: Logical reasoning is part of medical practice since its origins. Modern Medicine has included information-intensive tools to refine diagnostics and treatment protocols. We are introducing formal logic teaching in Medical School prior to Clinical Internship, to foster medical practice. Two simple examples (Acute Myocardial Infarction and Diabetes Mellitus) are given in terms of formal logic expression and truth tables. Flowcharts of both diagnostic processes help understand the procedures and to validate them logically. The particularity of medical information is that it is often accompanied by "missing data" which suggests to adapt formal logic to a "three state" logic in the future. Medical Education must include formal logic to understand complex protocols and best practices, prone to mutual interactions.